Persepsi Nasabah Terhadap Mekanisme Pelelangan Barang di PT.Gadai Syariah Solusi Makassar: Studi Kasus PT.Gadai Syariah Solusi Makassar - St. Fauziah Anwar; Sirajuddin, Sirajuddin; Muslihati, Muslihati; Katman, Muhammad Nasri (Jurnal Publikasi Ekonomi dan Akuntansi, 2026)
This study aims to analyze customer perceptions of the auction mechanism at Gadai Syariah Solusi Makassar. With the increasing number of customers involved in the auction process, it is important to understand how they perceive the effectiveness, transparency, and satisfaction with the service. The method used was qualitative research, collecting data from several customers at Gadai Syariah Solusi Makassar. The results indicate that the majority of customers are dissatisfied with the auction mechanism, but some understand and accept it during the auction process. Thus study is expected to provide recommendations for improving the effectiveness of pawnshop staff in providing customers with an understanding of the auction mechanism at Gadai Syariah Solusi Makassar, making it more user-friendly and transparent, thus increasing customer comfort and confidance in their transaction.